Chemical Dealloying Derived 3D Porous Current Collector for Li Metal Anodes. Issue 32 (24th May 2016) - Yun, Qinbai; He, Yan‐Bing; Lv, Wei; Zhao, Yan; Li, Baohua; Kang, Feiyu; Yang, Quan‐Hong
Abstract : A 3D porous Cu current collector is fabricated through chemical dealloying from a commerial Cu–Zn alloy tape. The interlinked porous framework naturally integrated can accommodate Li deposition, suppressing dendrite growth and alleviating the huge volume change during cycling. The Li metal anode combined with such a porous Cu collector demonstrates excellent performance and commerial potentials in Li‐based secondary batteries.